Against Intrinsic Interferers: A Critique of Kittle. (4th February 2017) - Choi, Sungho
Abstract: Kittle's recent paper brings into focus two interesting aspects of dispositions and employs them in an attempt to distinguish between cases where dispositions are subject to intrinsic interferers and cases where not. But I will argue below that Kittle doesn't succeed in this attempt. The upshot is that no such distinction is in sight, and this continues to be a troubling problem for those philosophers who uphold the possibility of intrinsic interferers with dispositions by insisting that, whilst some dispositions aren't subject to intrinsic interferers, others are.